Effect of testosterone on hepcidin, ferroportin, ferritin and iron binding capacity in patients with hypogonadotropic hypogonadism and type 2 diabetes. (18th July 2016) - Dhindsa, Sandeep; Ghanim, Husam; Batra, Manav; Kuhadiya, Nitesh D.; Abuaysheh, Sanaa; Green, Kelly; Makdissi, Antoine; Chaudhuri, Ajay; Dandona, Paresh
Summary: Context: As the syndrome of hypogonadotropic hypogonadism (HH) is associated with anaemia and the administration of testosterone restores haematocrit to normal, we investigated the potential underlying mechanisms. Design: Randomized, double‐blind, placebo‐controlled trial. Methods: We measured basal serum concentrations of erythropoietin, iron, iron binding capacity, transferrin (saturated and unsaturated), ferritin and hepcidin and the expression of ferroportin and transferrin receptor (TR) in peripheral blood mononuclear cells (MNC) of 94 men with type 2 diabetes. Forty‐four men had HH (defined as subnormal free testosterone along with low or normal LH concentrations) while 50 were eugonadal. Men with HH were randomized to testosterone or placebo treatment every 2 weeks for 15 weeks. Blood samples were collected at baseline, 3 and 15 weeks after starting treatment. Twenty men in testosterone group and 14 men in placebo group completed the study. Results: Haematocrit levels were lower in men with HH (41·1 ± 3·9% vs 43·8 ± 3·4%, P = 0·001). There were no differences in plasma concentrations of hepcidin, ferritin, erythropoietin, transferrin or iron, or in the expression of ferroportin or TR in MNC among HH and eugonadal men. Haematocrit increased to 45·3 ± 4·5%, hepcidin decreased by 28 ± 7% and erythropoietin increased by 21 ± 7% after testosterone therapy ( P < 0·05). There was no significant change in ferritin concentrations, but transferrin concentration increased while transferrin saturation and iron concentrations decreased ( P < 0·05). Ferroportin and TR mRNA expression in MNC increased by 70 ± 13% and 43 ± 10%, respectively ( P < 0·01), after testosterone therapy. Conclusions: The increase in haematocrit following testosterone therapy is associated with an increase in erythropoietin, the suppression of hepcidin, and an increase in the expression of ferroportin and TR.